2022
DOI: 10.3390/ijerph19063423
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Medication Review in Older People with Multimorbidity: A Comparative Analysis between Patients Living at Home and in a Nursing Home

Abstract: (1) Background: aging is associated with complex and dynamic changes leading to multimorbidity and, therefore, polypharmacy. A periodic medication review (MR) in frail older people leads to optimizing medication use. The aims of the study were to perform a comparative analysis of the impact of place of residence (own home versus nursing home) in a cohort of older patients on the characteristics of the baseline therapeutic plan and characteristics of the therapeutic plan after an MR; (2) Methods: Study with pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…This is also reported in the previous literature, with the specification that seniors living at home are more likely to have hospital admissions than those in institutions [ 90 ], and that a quarter of admissions of older people in residential facilities seems associated with their inability to self-administer drugs [ 91 ]. Moreover, in another study [ 92 ], senior residents showed a decreasing prevalence in both polypharmacy and complex therapies, with regard to those ageing at home. Our respondents also referred to the acceptance of moving to a nursing home to relieve family members of the burden of caring.…”
Section: Discussionmentioning
confidence: 99%
“…This is also reported in the previous literature, with the specification that seniors living at home are more likely to have hospital admissions than those in institutions [ 90 ], and that a quarter of admissions of older people in residential facilities seems associated with their inability to self-administer drugs [ 91 ]. Moreover, in another study [ 92 ], senior residents showed a decreasing prevalence in both polypharmacy and complex therapies, with regard to those ageing at home. Our respondents also referred to the acceptance of moving to a nursing home to relieve family members of the burden of caring.…”
Section: Discussionmentioning
confidence: 99%
“…The study has a quasi-experimental design (pre-post study) including a cohort of patients with multimorbidity (Community Older Patients cohort (COP cohort)) [ 16 , 23 ], in the Osona County, a mixed urban–rural district from Catalonia (Spain), with a three-month follow-up. Data were collected from June 2019 to October 2020.…”
Section: Methodsmentioning
confidence: 99%
“…An MR was carried out. Based on the current evidence, different criteria were used to determine inappropriate prescriptions in the most prevalent chronic conditions [ 23 ]: type 2 Diabetes Mellitus (T2DM) (guidelines of the American Diabetes Association (ADA) were applied [ 38 , 39 ]); hypertension and cardiovascular therapy [ 40 ]; dyslipidemia [ 41 ]; mental health and dementia (the recommendations of the European Association of Palliative Care were followed [ 42 ] and, the progressive dose decrease of chronic antipsychotic treatment was proposed in individuals who had not suffered behavioral disorders in the last 3–6 months [ 40 , 43 ]); and chronic pain (following Beers and STOPP criteria [ 44 46 ]). The STOPPFrail criteria were applied in patients identified at the end of life (according to NECPAL CCOMS-ICO© [ 34 ]) [ 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, evidence is still conflicting on whether desprescribing will have any effect on mortality as well as several factors are involved into the deprescribing process ( 34 ). A STOPPFrail-guided deprescribing plan in older nursing home residents with frailty and polypharmacy was successful in reducing polypharmacy but did not affect mortality, although the study may not have been sufficiently powered to assess this ( 35 ). As our study found higher mortality associated with hyperpolypharmacy in non-frail individuals, the question is whether deprescribing should be prioritized in individual's without frailty.…”
Section: Discussionmentioning
confidence: 99%